Konsistensi Light Weight Deflectometer Pusat Penelitian Jalan dan Jembatan (Pusjatan) Pada Jalan Tanah - Permana, Nesta; Syafier, Siegfried (JUTEKS : Jurnal Teknik Sipil, 2024)
Strong road infrastructure plays an important role in supporting community mobility, economic growth and regional development. Dirt road pavement is the type of pavement most often used in rural areas or areas with light to moderate traffic. Its advantages include lower costs compared to asphalt pavement as well as ease of construction. However, the main challenge of soil pavements lies in ensuring adequate consistency and stability, as the success of the pavement depends on proper compaction. Compaction of the subgrade road layer is a critical aspect that, if failed, can cause deformation and premature damage to the pavement. One of the tools used to test pavement stability and deflection is the Light Weight Deflectometer (LWD), which provides important data regarding the quality of the subgrade before the pavement is applied.